Restoring Vision in SLE: Successful Management of Lupus Retinopathy – A Case Report - Hasan, Md. Mehedi; Proma, Sanghita Banik; Imran, Sakan Binte; Hossain, Tanjila; Amiruzzaman, (Archives of Clinical and Medical Case Reports, 2025)
Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease which significantly affects multiple organs, including the ocular structures. Lupus retinopathy is one of those ocular manifestations, characterized by retinal ischemia and microvascular damage. Case Summary: During a study on retinal changes of Systemic Lupus Erythematosus (SLE) patients, we coincidently noticed some cases with lupus retinopathy, whose retinal changes were reversible after getting treatment for Systemic Lupus Erythematosus (SLE). This case report belongs to those cases. This case report presents a 38-year-old female who had initial complaints of blurred vision in right eye. The patient was concurrently diagnosed as Systemic lupus erythematosus (SLE), evidenced by polyarticular pain, fever and positive immunological and serological markers. The patient's visual symptoms significantly improved after receiving high dose glucocorticoids and immunosuppressive medications targeted towards her systemic symptoms of SLE. The follow-up exam showed that her vision had fully recovered and that his retinal lesions had resolved. Conclusion: This case highlights the significance of lupus retinopathy as a potential early ocular manifestation of Systemic Lupus Erythematosus (SLE). Recognizing lupus retinopathy in its initial stages can not only prevent severe visual impairment but also facilitate the early diagnosis of SLE. Regular ophthalmologic screening is therefore essential in patients at risk, as it can play a pivotal role in the timely diagnosis and management of SLE.